2016
DOI: 10.1590/1413-81232015217.05412015
|View full text |Cite
|
Sign up to set email alerts
|

Consumo alimentar e estado nutricional de mulheres em quimioterapia

Abstract: The objective behind this study was the analysis of food intake and the nutritional status of women with breast cancer (BC) undergoing chemotherapy (CT). The quantitative dietary evaluation was performed in accordance with Dietary Reference Intakes (DRI), whereas the qualitative evaluation was performed through the Brazilian Healthy Eating Index -Revised (BHEI-R). From among the total number of patients (n = 20), 60% (n = 12)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
1
8
0
19
Order By: Relevance
“…In addition, it is recognized that the distribution of body fat, especially abdominal fat, has more influence on metabolic risk factors than total body fat [33]. In the present study we found an association between waist circumference and breast cancer, which is similar to other studies conducted in Brazil [34][35][36] or in other countries [37,38]. Harvie et al [39] suggest that central obesity may be associated with a risk of breast cancer in premenopausal women, and other studies show association between abdominal obesity and risk of breast cancer in postmenopausal women [40,41].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it is recognized that the distribution of body fat, especially abdominal fat, has more influence on metabolic risk factors than total body fat [33]. In the present study we found an association between waist circumference and breast cancer, which is similar to other studies conducted in Brazil [34][35][36] or in other countries [37,38]. Harvie et al [39] suggest that central obesity may be associated with a risk of breast cancer in premenopausal women, and other studies show association between abdominal obesity and risk of breast cancer in postmenopausal women [40,41].…”
Section: Discussionsupporting
confidence: 91%
“…A alimentação adequada tem sido posta pelo WCRF 2 como recomendação para pacientes sobreviventes e apontada como aspecto modificável no sentido de prevenir recidiva da doença. Entretanto, para que essa qualidade no consumo alimentar exista entre mulheres sobreviventes do câncer de mama, há a necessidade de orientação nutricional adequada e acompanhamento desde o diagnóstico 26,27 . Em se tratando de extensão e propósito de processamento dos alimentos, Alves et al 3 levantam importante discussão sobre a necessidade de um ponto de corte que indique o que significa um consumo seguro de ultraprocessados.…”
Section: -9unclassified
“…Nos indivíduos com excesso de peso, a neoplasia de mama foi o diagnóstico mais presente, resultado semelhante ao encontrado nos estudos que avaliaram o estado nutricional de mulheres com carcinoma mamário [25][26][27] . Uma possível explicação para esse achado pode ser a relação com ingestão alimentar inadequada, alteração da taxa metabólica basal, restrição de atividade física e/ou menopausa 24 .…”
Section: Revistaunclassified